Emotional Design in Multimedia: Does Gender and Academic Achievement Influence Learning Outcomes? - Kumar, Jeya Amantha; Muniandy, Balakrishnan; Wan Yahaya, Wan Ahmad Jaafar (Malaysian Online Journal of Educational Technology, 2016)
This study was designed as a preliminary study (N = 33) to explore the effects of gender and academic achievement (Cumulative Grade Point Average-CGPA) on polytechnic students’ learning outcomes when exposed to Multimedia Learning Environments (MLE) designed to induce emotions. Three designs namely positive (PosD), neutral (NeuD) and negative (NegD) had similar contents and narrations but differed visually based on colors, images and font (size and style) in depicting the intended emotions. The learning outcomes evaluated are learning achievement, perceived intrinsic motivation and satisfaction. Overall, there was no significant difference between gender and CGPA when students were exposed to the emotionally designed MLE. However, male students were significantly more motivated and satisfied with the NegD design compared to the female students. A significant positive relationship was observed between intrinsic motivation and satisfaction and between gender and design. In addition, female students were found to prefer PosD design and male students, NegD design. Users of PosD and NegD design showed strong relationship between perceived intrinsic motivation and satisfaction. For learning achievement, high academic achievers performed better in the PosD design compared to other designs. No significant relationships were found between any of the variables for the NeuD design.